Aging and the Visual Perception of Motion Direction: Solving the Aperture Problem. (July 2018) - Shain, Lindsey M.; Norman, J. Farley
An experiment required younger and older adults to estimate coherent visual motion direction from multiple motion signals, where each motion signal was locally ambiguous with respect to the true direction of pattern motion. Thus, accurate performance required the successful integration of motion signals across space (i.e., accurate performance required solution of the aperture problem ) . The observers viewed arrays of either 64 or 9 moving line segments; because these lines moved behind apertures, their individual local motions were ambiguous with respect to direction (i.e., were subject to the aperture problem). Following 2.4 seconds of pattern motion on each trial (true motion directions ranged over the entire range of 360° in the fronto-parallel plane), the observers estimated the coherent direction of motion. There was an effect of direction, such that cardinal directions of pattern motion were judged with less error than oblique directions. In addition, a large effect of aging occurred—The average absolute errors of the older observers were 46% and 30.4% higher in magnitude than those exhibited by the younger observers for the 64 and 9 aperture conditions, respectively. Finally, the observers' precision markedly deteriorated as the number of apertures was reduced from 64 to 9.